THE IMPACT OF BUDGETARY POLICY OF THE REPUBLIC OF UZBEKISTAN ON MACROECONOMIC STABILITY - Mukhammadali Boymatov (Modern American Journals, 2025)
This thesis provides an in-depth analysis of the influence of budgetary policy in the Republic of Uzbekistan on macroeconomic stability in the period since its independence. Through an examination of fiscal frameworks, government revenues and expenditures, and the effectiveness of fiscal reforms, the research illustrates how budgetary decisions impact inflation, growth, public debt, and balance of payments. Combining theoretical perspectives, empirical data, and critical review of fiscal policy developments, the thesis underscores the strengths and weaknesses of Uzbekistan’s approach, the challenges posed by external shocks, and the prospects for sustainable stability. The article incorporates recent trends and global comparisons, drawing upon official documents, international financial institutions’ analyses, and academic literature, to provide thorough recommendations for further policy improvement.
Keywords: Budgetary Policy, Uzbekistan, Macroeconomic Stability, Fiscal Reform, Public Debt, Economic Growth, Inflation